Fluvial incision and coarse gravel redistribution across the modern Dead Sea shelf as a result of base‐level fall. Issue 11 (3rd June 2019) - Eyal, Haggai; Dente, Elad; Haviv, Itai; Enzel, Yehouda; Dunne, Thomas; Lensky, Nadav G.
Abstract: Global eustatic lowstands can expose vast areas of continental shelves, and occasionally the shelf edge and the continental slope. The degree of fluvial connectivity to receding shores influences the redistribution of sediments across these emerging landscapes. Shelf and slope emergence in the Dead Sea since the middle of the 20th century, offers a rare opportunity to examine evolution of stream connectivity in response to continuous base‐level decline. We characterize the connectivity evolution of two streams, using high‐resolution time series of aerial imagery and elevation models, field mapping, and grain‐size analyses. Our rich spatiotemporal dataset of evolving channel geomorphology, sediment transport conditions, and sediment redistribution, allows calculating potential coarse sediment mobility in response to base level decline. Following shelf emergence, alluvial fans first prograded onto the low‐gradient shelf under unfavourable conditions for transporting coarse sediment to the regressing shoreline. Then, with shelf and slope emergence, the two adjacent streams evolved differently. The smaller, more arid watershed still maintains its highstand delta progradation on the shelf and is practically disconnected from the receding lake. The larger catchment, heading in wetter environments and having a narrower shelf, has incised the shelf and renewed and gradually intensified the sediment transport from the highstand to the lowstand delta. Sediment mobilization to lowstand shorelines is controlled by the evolution of the channel profile and by the average speed of gravel transport (10s‐100s m yr ‐1 ). These findings from the Dead Sea are relevant to fluvial processes operating on continental shelves during glacial maxima. Streams would have commonly stored high proportions of their coarse sediment on the continental shelves rather than efficiently connecting with the lowstand level. Additionally, differences in sediment routing patterns should exist among nearby streams, primarily due to continental margin geometry and watershed hydrology. © 2019 John Wiley & Sons, Ltd. Abstract : We record a real‐time, natural, field‐scale response of fluvial systems to lake level fall in the Dead Sea – analogues to continental shelf and slope emergence, including the evolution of the fluvial processes and the onset and intensification of sediment bypass. We demonstrate that hydroclimatology and shelf geometry potentially produce high spatio‐temporal variability in patterns of sediment routing of adjacent streams during low levels. We also discuss implications for fluvial responses to global sea level fall.